Burnout and cognitive impairment: Associated with serum BDNF in a Chinese Han population. (March 2017) - He, S.C.; Zhang, Y.Y.; Zhan, J.Y.; Wang, C.; Du, X.D.; Yin, G.Z.; Cao, B.; Ning, Y.P.; Soares, J.C.; Zhang, X.Y.
Highlights: 30.5% of 712 healthy subjects in a general hospital were diagnosed for burnout. The burnout subjects showed lower cognitive performance. A decrease in BDNF serum level was found in burnout subjects. Decreased BDNF was positively associated with lower cognitive performance. BDNF had mediating effect in the relation between burnout and cognitive impairments. Abstract: Background: Some studies have demonstrated that subjects with chronic burnout showed cognitive impairments; however, cognitive performance in burnout has been under-investigated. Increasing evidence show that brain-derived neurotrophic factor (BDNF) plays a critical role in cognitive function. We hypothesized that decreased BDNF may be associated with cognitive impairments in burnout, which has not been investigated yet. The aim of the present study was to examine the association of BDNF with cognitive impairment in burnout. Method: Using a cross-sectional design, 712 healthy subjects were recruited from a general hospital and they were all measured with the Maslach Burnout Inventory (MBI). We assessed part of subjects on the repeatable battery for the assessment of neuropsychological status (RBANS) (n = 192) and serum BDNF levels (n = 127). Results: 30.5% of the subjects had burnout. Compared to those non-burnout subjects, the burnout subjects were younger, had significant lower BDNF levels (p = 0.003) and scored lower on immediate memory, RBANS total score and attention (all p < 0.05). Interestingly, after the Bonferroni correction, there were negative correlations between BDNF and MBI total score or reduced professional accomplishment (PA). Moreover, BDNF was positively associated with immediate memory, attention and RBANS total score. Further multiple regression analysis showed that BDNF was an independent contributor to the RBANS total score and attention, and BDNF and MBI depersonalization (DP) were independent contributors to immediate memory. In addition, there was mediating effect of BDNF in the relation between burnout and cognitive impairments. Conclusions: Our results suggest that burnout is associated with significant cognitive impairments and decreased BDNF. Moreover, decreased BDNF is associated with cognitive impairments in burnout.